2017
DOI: 10.1111/imj.13614
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 as a predictor of adverse renal outcomes in patients with immunoglobulin A nephropathy

Abstract: Initial serum GDF 15 level showed an inverse correlation with serum eGFR and was associated with worse renal outcome. Our results suggested that GDF 15 may play a role as a potential prognosticator in IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Moreover, in DN patients, high levels of GDF15 are associated with a decline in estimated glomerular filtration rate and faster progression to kidney failure [ 57 ]. Surely, the enhanced levels of GDF15 can deliver information about the deterioration of kidney function [ 60 , 61 , 62 ]. However, the suitability of GDF15 as a precise marker for kidney disease needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in DN patients, high levels of GDF15 are associated with a decline in estimated glomerular filtration rate and faster progression to kidney failure [ 57 ]. Surely, the enhanced levels of GDF15 can deliver information about the deterioration of kidney function [ 60 , 61 , 62 ]. However, the suitability of GDF15 as a precise marker for kidney disease needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…GDF-15 has also been associated with fibrosis in diseases of other organ systems such as dilated cardiomyopathy [28], systemic sclerosis [29], and chronic liver disease [30]. Two recent studies have shown GDF-15 to be associated with biopsy-proven fibrosis in the kidneys, the first in patients with IgA nephropathy [31] and the other in idiopathic membranous nephropathy [32]. GDF-15 might therefore also be a marker or a causative factor of kidney fibrosis that is responsible for decreased renal function in our pediatric cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Na et al [11] demonstrated that plasma GDF-15 has an inverse correlation with eGFR and is associated with poor renal outcomes in patients with IgA nephropathy, and Ham et al [10] reported similar trends in patients with idiopathic membranous nephropathy. Higher levels of GDF-15 predicted faster decline of renal function in patients with type 1 DM who have nephropathy [8] and starting dialysis in light chain amyloidosis patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GDF-15 has emerged as a biomarker for diagnosis and prediction of disease progression in various diseases, including cardiovascular and chronic inflammatory diseases [7]. Some studies have reported that higher GDF-15 levels are also associated with renal disorders such as diabetic nephropathy, idiopathic membranous nephropathy, and IgA nephropathy [8-11]. Other researchers have demonstrated that GDF-15 levels are correlated with prognosis of chronic kidney disease (CKD) [12, 13].…”
Section: Introductionmentioning
confidence: 99%